Self-Regulation, Compensation, and the Ethical Recruitment of Oocyte Donors - Levine, Aaron D. (The Hastings Center report, 2010)
Over the last couple of decades, oocyte donation has become common, important, and sometimes lucrative. Women who donate eggs are often offered fees, though ostensibly only to offset their expenses and limited to no more than USD10,000, following recommendations adopted by the fertility industry. Is the industry adhering to its recommendations? A study of advertisements published in college newspapers raises questions.